A contribution to the knowledge of Dryinidae from Late Eocene Baltic amber (Hymenoptera: Chrysidoidea), with description of new subfamily, Protodryininae subfam. nov. - Olmi, Massimo; Guglielmino, Adalgisa (Zootaxa, 2012)
A new subfamily, Protodryininae Olmi & Guglielmino, subfam. nov. with Protodryinus eocenicus Olmi & Guglielmino, gen.et sp. nov. and Lonchodryinus balticus, Olmi & Guglielmino, sp. nov. from subfamily Anteoninae are described from Balticamber. An updated new key to the world subfamilies of Dryinidae and a checklist of the species known from Baltic amber are given.